Evaluating the Blocking Probability and Optimizing the Placement of Wavelength Converters in WDM Optical Networks - et. al, Shruthi P C (International Journal of Control and Automation, 2019)
In the recent technology Wavelength Converters are the key components of Advanced Wavelength Division Multiplexing Network. In network design, the cost is very important considerable factor at the same time their optimization performance is considered. In Optical transmission techniques, the importance of Wavelength Converter, their intelligence and optimal placement have been found out in the research. In this paper, the simple analytical network model is designed, the blocking probability of the network is evaluated and placing the Wavelength Converter optimally at different nodes of the network with parameters like path, load of the link, traffic matrix of the network, Wavelength.